Neurocognitive Impairments (NCI) in bipolar disorder: Comparison with schizophrenia and healthy controls (2020)
Background: Neurocognitive impairments (NCI) are common in patients with bipolar I disorder. However, reports about the affected domains, outcomes and magnitude have been inconsistent. The aim of this study was to compare the magnitude (severity) and specificity (domains), of (NCI) in euthymic Bipolar I Disorder (BD) patients with a demographically and educationally matched sample of patients with schizophrenia in remission (SC) and healthy controls (HC). Methods: The Screen for Cognitive Impairment in Psychiatry (SCIP) was applied in this cross-sectional study, to all consecutive and consenting euthymic outpatients with bipolar I disorder (BD) (n = 76), remitted patients with schizophrenia (n = 130) and age and gender-matched healthy controls (HC) (n = 100). The cognitive tests done included Verbal List Learning-Immediate (VLT-I), Working Memory Test (WMT), Verbal Fluency Test (VFT), Verbal Learning Test-Delayed (VLT-D) and Processing Speed Test (PST). Within the bipolar group, the association between NCI and functioning was assessed. Results: There was a significant difference in the proportions of participants that had cognitive impairment from the 3 groups (37% (HC) vs. 71.1% (BD) vs. 91.5%(SC) (p=0.001) The BD group in comparison to the HCs did worse on all domains of the SCIP except WMT and PST. The BD group was not significantly different from the SC group in all neuropsychological domains of the SCIP except WMT. BD group significantly functions better than the SC group. The severity of depressive symptomatology and VLT-I were independent predictors of functioning in the BD group. Conclusion: Cognitive impairment affects almost all the neurocognitive domains of the BD group. The difference in NCI between euthymic BD patients and SC in remission are quantitative rather than qualitative.